Implementation of Guided Discovery Learning to Improve Chemistry Learning Outcomes of Class X TBSM 1 at SMK Negeri 2 Palembang - Cut Galuh Ayu Handira; Muhammad Hadeli; Rahma Aini (Pedagogy Review, 2022)
Abstract: Implementation of Guided Discovery Learning to Improve Chemistry Learning Outcomes of class X TBSM 1 at SMK Negeri 2 Palembang. The study is aimed to enhance the learning outcomes of chemistry on students class X TBSM 1 by implementing the Guided Discovery learning model. This study is conducted in two cycles; each cycle consists of two meetings. The data are obtained from using the observation sheet and an instrument of students’ learning outcomes test which is given every meeting. The enhancement of students’ learning outcomes can be observed from the average number of students’ learning outcomes before treatment (T0) in the amount of 62,86 with the mastery learning in the amount of 41,67%. The enhancement happens on cycle I (T1) becomes 68,72 with the mastery learning in the amount of 44,44% and on cycle II (T2) enhances into 87,45% with the mastery learning in the amount of 86,11%. Based on the result it is concluded that students’ learning outcomes achieve the mastery learning classically through the implementation of guided discovery learning model and students’ activities which happen to be enhancing as well.  Keywords: class treatment study, guided discovery model, students’ learning outcomes of chemistry.